Photothermal therapy with immune-adjuvant nanoparticles together with checkpoint blockade for effective cancer immunotherapy - Qian Chen (Nature Portfolio, 2016)
Photothermal therapy can induce an anti-tumour immune response by producing tumour-associated antigens. Here, the authors design a nanoparticle that simultaneously acts as a photothermal agent and an immune-adjuvant and demonstrate the anti-tumour efficacy in combination with anti-CTLA4 therapy in preclinical murine cancer models.